COVID-19, Public Procurement Regimes, and Trade Policy - Hoekman, Bernard; Shingal, Anirudh; Eknath, Varun; Ereshchenko, Viktoriya (World Bank, Washington, DC, 2021)
This paper analyzes a prominent dimension of the initial policy response to the COVID-19 pandemic observed in many countries: the imposition of export restrictions and actions to facilitate imports. Weekly data on the use of trade policy instruments during the first seven months of the COVID-19 pandemic (January-July 2020) are used to assess the relationship between the use of trade policy instruments and attributes of pre-crisis public procurement regulation. Controlling for country size, government effectiveness and economic factors, the analysis finds that use of export restrictions targeting medical products is strongly positively correlated with the total number of steps and time required to complete procurement processes in the pre-crisis period. Membership in trade agreements encompassing public procurement disciplines is associated with actions to facilitate trade in medical products. These findings suggest that future empirical assessments of the drivers of trade policy during the pandemic should consider public procurement systems.